Perbuatan Melawan Hukum Materiil Berfungsi Positif dan Berfungsi Negatif dalam Tindak Pidana Korupsi - Wildan Mustahqul Amri (Kajian Hukum, 2021)
The damage caused by corruption has been very severe, it has been outrageous. Corruption is not only detrimental to the state's finances, but has also damaged the morale of this nation, causing the ignorance of this nation. The culture of corruption has become like flesh and blood in the life of the people of the country. In Indonesia, corruption is synonymous with bad actions carried out by bureaucratic apparatus and people who are competent in the bureaucracy. Corruption can be sourced from the weaknesses contained in the political system and the state administration system with the bureaucracy as the main tool. This paper focuses on how do acts against the material law have a positive and negative function in corruption. The research conducted in this paper is doctrinal researchand library research. This paper concluded that criminal acts of corruption there are acts against material law in positive and negative functions. Negative function means that even though an act has fulfilled the formulation of the law as a criminal act, its unlawful nature can be removed because of provisions outside the law that justify the act and have a positive function if the opposite occurs.